2014
DOI: 10.1371/journal.pone.0105797
|View full text |Cite
|
Sign up to set email alerts
|

Zn-Responsive Proteome Profiling and Time-Dependent Expression of Proteins Regulated by MTF-1 in A549 Cells

Abstract: Zinc plays a critical role in many biological processes. However, it is toxic at high concentrations and its homeostasis is strictly regulated by metal-responsive transcription factor 1 (MTF-1) together with many other proteins to protect cells against metal toxicity and oxidative stresses. In this paper, we used high-resolution two-dimensional gel electrophoresis (2DE) to profile global changes of the whole soluble proteome in human lung adenocarcinoma (A549) cells in response to exogenous zinc treatment for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 54 publications
3
24
0
Order By: Relevance
“…Notably, the Mtf-1 gene is essential, as Mtf-1 knock-out (KO) mice die in utero due to liver degeneration and oedema (Günes et al 1998). MTF-1 regulates the expression of several genes, including those encoding placenta growth factor (Green et al 2001), several zinc transporters (Zhao et al 2014), the human prion protein (Bellingham et al 2009), and mir132 miRNA (Lee et al 2007). Knocking-down MTF-1 with siRNAs changes the transcriptional response to zinc for over 1000 genes (Hogstrand et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the Mtf-1 gene is essential, as Mtf-1 knock-out (KO) mice die in utero due to liver degeneration and oedema (Günes et al 1998). MTF-1 regulates the expression of several genes, including those encoding placenta growth factor (Green et al 2001), several zinc transporters (Zhao et al 2014), the human prion protein (Bellingham et al 2009), and mir132 miRNA (Lee et al 2007). Knocking-down MTF-1 with siRNAs changes the transcriptional response to zinc for over 1000 genes (Hogstrand et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The proteins Hsp90α and hnRNPA1 were found to respond to metal exposure (Barque, Abahamid, Chacun, & Bonaly, ; Padmini & Rani, ; Zhao et al, ; Zhao et al, ). The kinetic responses and differential expression patterns of Hsp90α and hnRNPA1 were observed when A549 cells were incubated with CdSO 4 for 1, 3, 6, 9, 12 or 24 hours.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, we have examined the time‐dependent changes in the expression of proteins and the proteome involved in Zn homeostasis, and we elucidated the mechanism of the process. Our results showed that A549 cells present a kinetic response to exogenous zinc sulfate (ZnSO 4 ) stress in four conservatively time‐dependent manners and that exogenous ZnSO 4 more predominantly reduced the expression of proteins in cells after 24 hours than 9 hours (Zhao et al, ; Zhao et al, ). In the present work, to unclose further the difference of response mechanisms of different cells to various metals ions, we profiled the toxicokinetic response of the proteome in A549 cells exposed to extracellular CdSO 4 at different time points using 2DE coupled with silver staining.…”
Section: Introductionmentioning
confidence: 85%
“…In addition, the metabolism of As 3+ to As 5+ affects the reduction of H 2 O, which generates H 2 O 2 , and some metabolic intermediates, such as dimethyl arsine peroxyl radical. 124 OS contributes to As 3+ -induced kinase activation that leads to S21 phosphorylation of the enhancer of zeste homolog 2 (EZH2) protein, and is present in the direct interaction of the activated Akt and EZH2. Furthermore, OS appears to be able to induce cytoplasmic localization of the phosphorylated and the nonphosphorylated EZH2 protein in As 3+ -treated cells.…”
Section: As Implicationmentioning
confidence: 99%
“…These proteins show maximum changes in their expression by Zn treatment, and the proteome of A549 cells possibly exhibits significant changes to exogenous Zn ions exposure. 124 Zn and the ionophore compound pyrrolidinedithiocarbamate (PDTC) treatment provoke apoptosis, which is associated with ROS-dependent nuclear translocation of the mitochondrial factor AIF. P53 degradation plays an important role in fibroblast resistance to Zn/PDTC.…”
mentioning
confidence: 99%